Fabrication of nanocatalysts as nanozymes-based biosensors for the detection of glucose and ascorbic acid - Chavalala, Ridge Nhlamulo (Rhodes University, Faculty of Science, Department of Chemistry)
Monitoring and detection of biomolecules is of great importance for prevention, identification, and treatment of various diseases. Therefore, developing convenient, highly portable, and efficient methods for the detection and monitoring of biomolecules is of importance. The development of nanozymes-based biosensors for the detection of glucose and ascorbic acid (AA) was achieved. Noble metal or platinum group metal nanoparticles (NPs) of gold (AuNPs), palladium (PdNPs), and gold/palladium (Au/PdNPs) were fabricated on silica nanoparticles (SiO2NPs) coated on hydroxylated indium tin oxide (ITO-OH). The formed ITO-SiO2NPs surface acted as the absorbent for noble NPs. Prior to noble metal adsorption, ITO-SiO2NPs was first coated with 3-mercaptoproyltrimethoxy-silane (MPTMS) to introduce a thiol functional groups for the chemisorption of AuNPs, PdNPs, and Au/PdNPs. The various surfaces were labeled as ITO-SiO2-prS-AuNPs, ITO-SiO2-prS-PdNPs, and ITO-SiO2-prS-Au/PdNPs. A simple, easily recoverable and high selectivity colorimetric assay towards glucose detection was fabricated based on the peroxidase-like activity of ITO-SiO2-prS-PdNPs on the oxidized 3,3',5,5'-tetramethylbenzidine (TMB). A selective colorimetric assay for AA detection was fabricated based on the reduction effect of AA on the oxidized TMB using ITO-SiO2-prS-Au/PdNPs. The nanozymes-based bionsensors that exhibit good linear concentration range were successfully prepared and used to detect glucose and AA in (new-born calf serum, NCS), as real samples or complex matrix.
Keywords: Nanoparticles; Biosensors; Biomolecules; Glucose; Vitamin C; Colorimetric assay